Food Safety Training and Food Safety Practices Among Street Vendors at Public Elementary Schools - Apriliya Adha; Zakianis Zakianis; Laila Fitria; Haryoto Kusnoputranto; Halik Hadi; Surya Kusuma Purba (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In Indonesia, only about ?30% of street vendors in schools implement good food safety practices. This can have a negative impact on health that can lead to foodborne disease. Food safety practices are still low, especially for street vendors at public elementary schools in Tanjung Balai City, so food safety training is needed. Proper food safety training will be very influential in reducing the incidence and overall rate of foodborne illnesses. The purpose of this study is to analyze the relationship between food safety training and food safety practices in street vendors at public elementary schools in Tanjung Balai City. Methods: This study uses a cross-sectional design. The research is located at public elementary schools in Tanjung Balai City during November 2024. The sample involved 335 street vendors from 67 elementary schools. Data collection uses a questionnaire accompanied by interviews with respondents who have signed informed consent. This research has obtained permission from the Research Ethics and Community Service Commission, Faculty of Public Health, University of Indonesia. Results: The results of the study show that most street vendors at Public Elementary Schools have poor food safety practices as much as 61.2% and have never participated in food safety training as much as 80%. Factors that were significantly related to food safety practices were food safety training, gender, age, knowledge and attitudes related to food safety (p-value <0.05), while education level, Vending Duration, and monthly income did not show significant results. The results of the multivariate test showed a significant relationship between food safety training and food safety practices after being controlled by gender, age, education and knowledge related to food safety (AOR=3.00; CI: 1.25-7.24; p=0.01). Conclusion: Food safety training is significantly related to food safety practices. Therefore, it is hoped that the relevant agencies can provide comprehensive food safety training to all street vendor in public elementary school’s environment”.